Using volunteers to improve access to community rehabilitation in palliative care: the St Christopher's Living Well at Home Team - Preston, Gail; Rampes, Sanketh; Bayly, Joanne; Rice, Helena Talbot; Angelova, Ralitsa; Richardson, Heather; Maddocks, Matthew (Frontiers in Rehabilitation Sciences, 2023)
Background UK hospices often provide outpatient rehabilitation services for people with advanced progressive illness. However, some people are unable to travel, leading to inequity in rehabilitation access. Objectives The Living Well at Home Team (LWAHT) at St Christopher's Hospice aimed to evaluate whether using volunteers to support rehabilitation in peoples’ homes improved the reach of rehabilitation for people living in underserved localities and if it supported people to optimise their functional independence. Methods This service improvement project evaluated hospice rehabilitation uptake during the implementation of volunteer-supported community rehabilitation. Following assessment by an LWAHT therapist, eligible people were matched with a trained volunteer who supported four to eight rehabilitation sessions in the person's home. The evaluation assessed uptake of the rehabilitation sessions. Mobility, wellbeing, and goal attainment outcomes were assessed by the Life-Space Assessment (LSA), General Health Questionnaire (GHQ), and Goal Attainment Scale (GAS), respectively. Results In the first year, 183 patients were referred to the LWAHT; 123 were assessed and 96 received rehabilitation including 56 who were matched with a volunteer. Following volunteer support, patients reported significant improvements in mobility [LSA median 20 (IQR, 3.5–27.8)], general health [GHQ −2 (−5.25 to 0)], and achievement of goals [GAS T-score +8 (0–18.4)]. Conclusions It was feasible to support community rehabilitation using hospice volunteers for people with advanced progressive illness. The LWAHT service also increased the uptake of hospice centre-based rehabilitation. Further work should test efficacy and identify patients requiring additional professional input. Key message This is the first known study reporting on the use of trained rehabilitation volunteers to extend the reach of hospice rehabilitation services. People with limited access to the hospice, because of geographical location or personal circumstances, valued and benefited from tailored rehabilitation supported by the volunteers in their own homes.